2018
DOI: 10.5114/ada.2018.76228
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation protein products and serum total oxidant/antioxidant status levels in rosacea

Abstract: IntroductionRosacea is a chronic, inflammatory dermatosis which develops due to the effect of genetic and environmental factors.AimTo evaluate the oxidative stress in rosacea patients by measuring serum total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI) and advanced oxidation protein products (AOPP) levels in our study.Material and methodsOur study included rosacea patients and healthy volunteers aged between 18 and 65 years. Total antioxidant status, TOS and AOPP levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 12 publications
1
22
2
Order By: Relevance
“…Previous studies showed that ROS activity in biopsy samples taken from individuals with rosacea was found to be higher in rosacea lesion skin 16,17 . In a recent study, serum total oxidant status (TOS), total antioxidant status (TAS), oxidative stress index (OSI), and advanced oxidation protein products (AOPP) in rosacea patients were compared with the HCs, and while no differences were found between two groups in terms of OSI levels, TOS, TAS, and AOPP levels were reported to be significantly higher in patient group 18 . In our study, statistically significantly low serum bilirubin and UA levels of rosacea patients when compared with the HC group sustain the view that oxidative stress‐antioxidant balance changes in favor of oxidative stress in rosacea disease and in turn may cause inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that ROS activity in biopsy samples taken from individuals with rosacea was found to be higher in rosacea lesion skin 16,17 . In a recent study, serum total oxidant status (TOS), total antioxidant status (TAS), oxidative stress index (OSI), and advanced oxidation protein products (AOPP) in rosacea patients were compared with the HCs, and while no differences were found between two groups in terms of OSI levels, TOS, TAS, and AOPP levels were reported to be significantly higher in patient group 18 . In our study, statistically significantly low serum bilirubin and UA levels of rosacea patients when compared with the HC group sustain the view that oxidative stress‐antioxidant balance changes in favor of oxidative stress in rosacea disease and in turn may cause inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…Derangements in the oxidant/antioxidant system have been identified in rosacea 4,5,9 . Erdogan et al 24 interpreted the oxidant stress condition by assessing serum total oxidant/antioxidant status, advanced oxidation protein products, and oxidant stress index in rosacea patients and found significantly elevated levels of each, supporting the notion of oxidant stress acting in the pathogenesis of rosacea. More recently, Sener et al 25 investigated thiol/disulfide homeostasis (which has important roles in the antioxidative process) in patients with rosacea.…”
Section: Discussionmentioning
confidence: 96%
“…The contribution of antioxidant system in patients with rosacea has likewise been shown at the genetic level. 47 In particular, the Glutathione-S-transferase (GST)M1 and GSTT1 genes which encode for enzymes neutralizing toxic oxidative intermediates, were found to have null mutations in a high proportion of patients with rosacea. 48…”
Section: Genetic Factorsmentioning
confidence: 99%